2007
DOI: 10.1080/09647770701757708
|View full text |Cite
|
Sign up to set email alerts
|

Museum Websites and Museum Visitors: Before and After the Museum Visit

Abstract: This article presents results from an exploratory survey (administered to more than 1,200 visitors at nine different online museums) that addressed questions about the role of museum websites in the lives of museum visitors. The results provide details about the use of museum websites before and after the museum visit, and indicate that online visitors frequently use museum websites to complement their visits to physical museums. The article helps museum researchers and professionals better understand the cycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
0
16

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(88 citation statements)
references
References 16 publications
4
68
0
16
Order By: Relevance
“…Studies have shown concerns about a negative effect of the provision of extensive information online on visitor numbers and visitor satisfaction to be unfounded, however [123][124][125]. Visitors tend to use the amount and quality of information provided by an institution of public memory as a proxy for the quality and type of a visitor's experience on site, and the number of visits is positively correlated with the extent and quality of an institution's online presence, even when a virtual exhibit duplicates many elements of what is shown online.…”
Section: The Significance Of the Internetmentioning
confidence: 99%
“…Studies have shown concerns about a negative effect of the provision of extensive information online on visitor numbers and visitor satisfaction to be unfounded, however [123][124][125]. Visitors tend to use the amount and quality of information provided by an institution of public memory as a proxy for the quality and type of a visitor's experience on site, and the number of visits is positively correlated with the extent and quality of an institution's online presence, even when a virtual exhibit duplicates many elements of what is shown online.…”
Section: The Significance Of the Internetmentioning
confidence: 99%
“…With the existence of online technology, museums expand their services by allowing the consumers to visit the official website of museum, comparing the exhibitions and embracing the history and artifacts together in an online way (Hume & Mills, 2011). By this means, Marty (2007) points out that visitors of physical museums should feel similarly inspired to visit the museum's website, using the website as a bridge to connect their pre-visit and postvisit activities by learning more about the museum and its collections.…”
Section: Enhancement Of Experiences In Museums Through Technologymentioning
confidence: 99%
“…However, it is critical to understand consumer behavior depending on changes of new information technologies, because social media marketing is playing an increasingly important role in hospitality and tourism field (Chan & Guillet, 2011;Xiang & Gretzel, 2010). Additionally, according to Marty (2007), museums can achieve innovative solutions to complex problems by using social media as a platform and museums as a laboratory for extending partnership and building capacity by creatively connecting design communities. Recently, social media has become the method of statement in the 21 st century, enabling people to express their beliefs, ideas, and manner in an absolute new way (Saravanakumar & Suganthalakshmi, 2012).…”
Section: Museums In Social Mediamentioning
confidence: 99%
“…Motivation for online heritage consumption has been linked first and foremost to remote access (Booth, 1998), but also to academic research, creative reuse, educational use, commemorative use, personal enjoyment, preservation and commercial use . Most museum website traffic is linked to planning a visit onsite, though viewing collections online has being found complementary to the physical museum visit (Marty, 2007).…”
Section: Cultural Consumptionmentioning
confidence: 99%